Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

População da Ilha de Moçambique queixa-se de cobranças ilícitas na maternidade - Televisão de Moçambique TVM (Televisão de Moçambique TVM, 2016)
Primeira sessão do dia aberto ao cidadão, uma iniciativa do conselho municipal da ilha de Moçambique para escutar as questões que atinjem os cerca de 50mil habitantes da primeira capital de Moçambique. As reuniões são realizadas nas comunidades para que de forma franca e aberta os munícipes possam apresentar os seus problemas
Keywords: G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Place, Time and Experience: Barriers to Universalization Of Institutional Child Delivery in Rural Mozambique - Agadjanian, Victor; Yao, Jing; Hayford, Sarah R (International perspectives on sexual and reproductive health, 2016)
CONTEXT: Although institutional coverage of childbirth is increasing in the developing world, a substantial minority of births in rural Mozambique still occur outside of health facilities. Identifying the remaining barriers to safe professional delivery services can aid in achieving universal coverage. METHODS: Survey data collected in 2009 from 1,373 women in Gaza, Mozambique, were used in combination with spatial, meteorological and health facility data to examine patterns in place of delivery. Geographic information system-based visualization and mapping and exploratory spatial data analysis were used to outline the spatial distribution of home deliveries. Multilevel logistic regression models were constructed to identify associations between individual, spatial and other characteristics and whether women's most recent delivery took place at home. RESULTS: Spatial analysis revealed high- and low-prevalence clusters of home births. In multivariate analyses, women with a higher number of clinics within 10 kilometers of their home had a reduced likelihood of home delivery, but those living closer to urban centers had an increased likelihood. Giving birth during the rainy, high agricultural season was positively associated with home delivery, while household wealth was negatively associated with home birth. No associations were evident for measures of exposure to and experience with health institutions. CONCLUSIONS: The results suggest the need for a comprehensive approach to expansion of professional delivery services. Such an approach should complement measures facilitating physical access to health institutions for residents of harder-to-reach areas with community-based interventions aimed at improving rural women's living conditions and opportunities, while also taking into account seasonal and other variables.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Pas, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found